Analyzing Paint Consumer Satisfaction with SERVQUAL, CSI, and IPA - Muhammad Reza Widianto; Akhmad Wasiur Rizqi (G-Tech: Jurnal Teknologi Terapan, 2026)
Service quality is a critical factor in maintaining customer satisfaction and competitiveness in a dynamic business environment. This study aims to analyze customer satisfaction by integrating the Service Quality (SERVQUAL), Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA) methods. Data were collected through questionnaires distributed to 113 respondents and analyzed using validity and reliability tests. The SERVQUAL results indicate positive gaps across all five dimensions: tangibles, reliability, responsiveness, assurance, and empathy, suggesting that perceived service exceeds customer expectations. Responsiveness shows the highest gap (0.55), while empathy records the lowest (0.48). The CSI value of 79.36% places overall customer satisfaction in the “Satisfied” category. Furthermore, IPA mapping identifies priority attributes for improvement as well as those that should be maintained. These findings imply that although service quality is generally good, enhancing empathy and sustaining responsiveness are necessary to achieve a Very Satisfied level of customer satisfaction. Finally, this research contributes to decision-making strategies for short-term service improvement by offering a clear prioritization map that can support more effective and targeted managerial actions.